The bleisure tourism trend and the potential for this business-leisure symbiosis in Porto - Pinho, Micaela (2021)
The combination of business and leisure into one trip – bleisure – is becoming popular. This segment has received a strong boost, especially from Millennials. The purpose of this paper is to analyze the bleisure tourism phenomena and the potential for this business-leisure symbiosis in Porto. A mixedmethod approach was adopted through a Delphi technique to explore tourism stakeholder’s perceptions concerning both the city’s opportunities and strategies that should be followed to boost the bleisure tourism sector. The assets identified as very important for the development of bleisure tourism in the city were unique gastronomy, good wines, the historical center and local people’s hospitality. Nevertheless, improve human resource qualification, increase flight connections, enhance local heritage and urban regeneration and fostering collaboration networks between local stakeholders are strategic actions that merit more attention. Many studies have been conducted from the perspective of business tourism activities and impacts; few have been conducted from the bleisure tourism perspective and none have been conducted from the perspective of bleisure tourism in the city of Porto. This work represents the first attempt to elicit experts’ opinions about the potential of Porto to develop the bleisure tourism segment. This study aims to contribute to better understanding how destinations can take advantage of this niche segment of the tourism market, which kind of touristic assets can be valued and which specific destination attributes should be considered.